Analysis of leisure activities for disabled people aged ≥65 as a basis for planning health education diagnosis - Kamusińska, Elżbie; Lelonek, Barbara (Polish Journal of Public Health, 2011)
Introduction. Health education is a process in chich people learn to take care of their own health and the health of community in which they live. The elderly with health disorders with permanent disabilities are particularly import ant recipients of health education.Aim. Analysis of free time for the disabled aged ≥ 65 with a purpose of using this area of life in health education.Material and methods. The study included 122 patients treated in rehabilitation wards after brain stroke, hip joint Or knee replacement. The research population was selected on the basis of deliberate selection. The method of diagnostics survey, interview technique and the author’s interview questionnaire for disabled people were used, which included questions connected with leisure time. The resulting material was subjected to statistical and descriptive analysis.Results. Most people (89.4%) changed leisure activities in the aftermath of illness or surgery. They mostly appreciated their free time spent with family (77.0%), 12.3% chose the moments of solitude, and 10.7% spent time with friends. Among all the activities during leisure time, passive forms of recreation were dominant (81.2%); watching TV (27.2%), listening to the radio (19.2%), praying (17.5%) or Reading newspapers (17.2%). Active forms of recreation were accounting for 18.8% of all activities, mainly wal king (44.8%), social and family meeting (37.2%).Conclusion. There is a possibility of using free time of the disabled elderly for the purpose of health education. In planning this, distinction of the elderly age, methodology of persons’ education in their late adulthood, WHO recommendations for promoting seniors’ health education and individual needs of recipients should be considered.